ENHANCING TECHNICAL AND VOCATIONAL EDUCATION PROGRAMME FOR SUSTAINABLE CAPACITY BUILDING IN NIGERIA - Oviawe, Jane Itohan; Aluyor, Patience (Sokoto Educational Review, 2020)
The paper examined ways of enhancing Technical and Vocational Education (TVE) programmes for sustainable capacity building in Nigeria. It considered building capacity as economic capacity building because it increases the capability of any developed or developing society to improve trade, employment, economic development and quality of life. Capacity is seen as the proven ability of key actors in a society to achieve socioeconomic goals on their own. For sustaining capacity building in Nigeria, sufficient financial resource must be released to meet the capital and recurrent monitoring system TVE programmes. Emerging issues in TVE in Nigeria highlighted in this paper include: parental influence due to misconception, inadequacy of training equipment and facilities, and lack of relevant curriculum. Finally, this paper recommends among others that: Government at all levels should mount elaborate enlightenment campaigns on the essence of TVE for self-reliance, prestige and capacity building as way forward in enhancing TVE for effective capacity building.